Edukasi Moral Seksual dan Kesehatan Reproduksi Anak Remaja di Desa Belung Poncokusumo - Anaqoh Taqiyyah; Bening Sih Kinanti; Muhammad Farhan; Muhammad Nasrul Rafa Nugraha; Samudera Aria Putra (Peradaban Journal of Community Service, 2025)
The "Taking Care of My Own Body: Child and Adolescent Reproductive Health" program was implemented in Belung Village, Poncokusumo, to address the paucity of sexual education and the high prevalence of early marriage. This program aimed to provide interactive and age-appropriate insights into the importance of maintaining reproductive health. The program's implementation involved a pre-test, educational sessions, focus group discussions (FGDs) facilitated by a psychology expert, and a post-test. Evaluation results demonstrated a significant increase in participants' understanding of sexual morality and reproductive health, as evidenced by the post-test outcomes. This program contributes to fostering adolescents' awareness of maintaining their physical health and making informed decisions in the future. It is recommended to provide supplementary learning materials for home use to reinforce participants' independent understanding.Program kerja "Taking Care of My Own Body: Kesehatan Reproduksi Anak dan Remaja" di Desa Belung, Poncokusumo, dilaksanakan untuk mengatasi minimnya edukasi seksual dan tingginya angka pernikahan usia dini. Bertujuan memberikan wawasan interaktif dan sesuai usia tentang pentingnya menjaga kesehatan reproduksi, program ini melibatkan pre-test, edukasi materi, diskusi kelompok (FGD) dengan ahli psikologi, dan post-test. Hasil evaluasi menunjukkan peningkatan signifikan pemahaman peserta terkait moralitas seksual dan kesehatan reproduksi. Program ini berkontribusi dalam membangun kesadaran remaja untuk menjaga kesehatan tubuh dan membuat keputusan bijak di masa depan. Disarankan penyediaan materi pembelajaran lanjutan di rumah guna memperkuat pemahaman mandiri